Diverse Manifestation of Acromegaly With Suspicion of Ectopic GHRH Secretion. Report of Two Cases - Godlewska, Magdalena (J Endocr Soc, 2021)
Introduction: Acromegaly can rarely be caused by an ectopic production of GH or GHRH by various neoplasms, most commonly neuroendocrine tumors of pancreatic or pulmonary origin. Squamous cell carcinoma of the lung has not been associated with ectopic GHRH secretion yet. The authors present two cases of acromegaly with suspicion of GHRH ectopy. Presentation of the Cases: Case 1. A male born in 1945 presenting with typical morphologic features of acromegaly. Pituitary MRI revealed a cuneatic-shaped, hypointense focal lesion (8x7x6 mm) in the right posterior part of the anterior pituitary lobe, radiologically interpreted as either hyperplasia of the intermediate lobe or atypical adenoma in a normal-sized pituitary. IGF-1 and no suppression of GH secretion after oral glucose load were observed. Furthermore, a polycyclic tumor in the 2(nd) segment of the right lung with pathological metabolic activity in 18FDG- PET/CT was discovered. Ga(68)- DOTA TATE PET/CT revealed no pathological accumulation of the tracer. After upper right lobectomy, squamous cell carcinoma, non-keratinizing, G3, with a negative immunohistochemical reaction for GH was confirmed. IHC for GHRH and serum GHRH have been scheduled. After surgery and chemotherapy, no biochemical remission of acromegaly was observed and the pituitary MRI showed stable radiological image of the pituitary tumor, suggesting rather a possible metastasis to the pituitary. Due to unfavorable prognosis, the patient was disqualified from neurosurgical resection of the pituitary tumor. Case 2. a male born in 1948 with typical symptoms of acromegaly, elevation of IGF-1 and no suppression of GH in OGTT. Due to MRI contraindications, only CT of the head was performed- it revealed partially empty sella, compressed pituitary with maximal diameter 3 mm and no focal lesions. Treatment with somatostatin analogue was introduced, however, only partial biochemical control was achieved. Ga(68)- DOTA TATE PET/CT performed after 8 years showed pathological expression of somatostatin receptors in the pancreatic tail. Abdominal CT confirmed a focal lesion in this location, 14x9 mm, with a strong enhancement after contrast administration, suggesting a neuroendocrine tumor. The patient refused to undergo any invasive procedures and remains treated with SRL. Serum GHRH has been scheduled. Conclusion: The authors report two cases of ectopic acromegaly suspicion, with an ambiguous clinical and radiological presentation. In unclear cases of acromegaly, ectopic production of GHRH should be taken into consideration.